Synchronous oceanic spreading and continental rifting in West Antarctica. Issue 12 (21st June 2016) - Davey, F. J.; Granot, R; Cande, S. C.; Stock, J. M.; Selvans, M.; Ferraccioli, F.
Abstract: Magnetic anomalies associated with new ocean crust formation in the Adare Basin off north‐western Ross Sea (43–26 Ma) can be traced directly into the Northern Basin that underlies the adjacent morphological continental shelf, implying a continuity in the emplacement of oceanic crust. Steep gravity gradients along the margins of the Northern Basin, particularly in the east, suggest that little extension and thinning of continental crust occurred before it ruptured and the new oceanic crust formed, unlike most other continental rifts and the Victoria Land Basin further south. A preexisting weak crust and localization of strain by strike‐slip faulting are proposed as the factors allowing the rapid rupture of continental crust. Key Points: Onset of seafloor spreading is temporally coincident with rupture of the adjacent continental crust Rifted continental crust has a very sharp continental‐oceanic crustal boundary Continuity of seafloor spreading anomalies across the morphological continental shelf edge